Peculiarities of social workers’ and social pedagogues’ psychological empowerment in the aspects of self-determination theory and demographic variables - Kepalaitė, Albina; Vaitkevičienė, Asta; Drungėlaitė, Eglė (Social Welfare: Interdisciplinary Approach, 2018)
Social workers’ and social pedagogues’ sense of power is very important for providing social assistance and support to clients and learners. Sense of power depends on meeting the needs of autonomy, competence and relatedness. Failure to meet these needs due to lack of reward, punishments or cultural rituals causes reduces or completely restricts the subjective experience of power, increasing defensiveness and psychopathology. Social workers and social pedagogues provide social assistance and support to their clients and learners based on the empowerment strategy. It is therefore important to investigate whether the very social workers and social pedagogues feel empowered. This study aims to disclose social workers’ and social pedagogues’ psychological empowerment peculiarities with regard to demographic characteristics, gender, profession, qualification category and the occupied share of the post.